Provent therapy for obstructive sleep apnea: Impact of nasal obstruction. (17th April 2015) - Friedman, Michael; Hwang, Michelle S; Yalamanchali, Sreeya; Pott, Thomas; Sidhu, Mandeep; Joseph, Ninos J.
Abstract : Objectives/Hypothesis: Determine the impact of nasal obstruction on efficacy, success, and adherence of Provent therapy in patients with obstructive sleep apnea (OSA). Study Design: Prospective, two‐arm, clinical pilot study at a single clinical site. Methods: Patients with OSA who failed continuous positive airway pressure therapy were divided into two treatment arms: arm 1 were patients with no complaints of nasal obstruction and <50% nasal obstruction on exam, and arm 2 were patients with occasional complaints of nasal obstruction and 50% to 80% nasal obstruction on exam. Sleep testing at home was performed prior to the trial and on day 10 of the study with the use of Provent. Results: Apnea‐hypopnea index (AHI) decreased significantly from 20.5 ± 14.8 to 11.5 ± 16.6 ( P  < .001) in our total patient population. Patients in arm 1 had statistically significant improvement in their AHI (18.1 ± 13.0 to 7.4 ± 10.1, P  < .001), oxygen desaturation index (ODI) (16.3 ± 10.8 to 8.2 ± 9.0, P  < .001), and minimum oxygen saturation (81.3% ± 6.7% to 86.9% ± 5.6%, P  = 0.008) from baseline sleep study to sleep study 2. Patients in arm 2 had improvements in their AHI (23.4 ± 16.6 to 16.5 ± 21.4), ODI (21.5 ± 14.8 to 17.0 ± 16.0) and minimum 02 %. However, none of these reached statistical significance. Conclusions: In this study, Provent therapy had a high failure rate. Patients without nasal obstruction showed greater improvements using Provent than patients with obstruction. Correction of nasal obstruction may be a useful prerequisite for treatment with Provent. Level of Evidence: 2B. Laryngoscope, 126:254–259, 2016